APLIKASI STRATEGI KOMUNIKASI PEMASARAN SURAT KABAR HARIAN RAKYAT BENGKULU DALAM MENJARING PENGIKLAN - Vethy Octaviani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2014)
The picture of reality formed by the mass media was expected to underlie the response and attitude of the public towards various social conditions. It will indirectly affect the domestic firms, because in any case, they must be prepared to compete with other similar companies as well as the need to have courage in the face of competition from multinational companies that operate and are located in various areas. In this study the researcher used theories derived from sources that can be used as a reference. Data were collected by using interview techniques and data analysis. From the research, it’s known that the application of marketing communications strategy in Harian Rakyat Bengkulu was to attract advertising. The applied strategies was chosen by the needs, it means that the application of the strategy used is not too theoretical cultivated and made as simple as possible and inspired by the vision of the company. Basically every company (in this case Harian Rakyat Bengkulu) needed to apply marketing communication strategy in the company's vision and mission more effectively. Without the application of marketing communication strategy, the company most likely would not run well.Keywords: company, marketing communications strategy, advertiser